2022
DOI: 10.3390/vaccines10122022
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox Knowledge and Vaccine Hesitancy of Czech Healthcare Workers: A Health Belief Model (HBM)-Based Study

Abstract: Background: The recent human monkeypox virus (HMPXV) outbreak in non-endemic countries that started in May 2022 has raised concerns among public health authorities worldwide. Healthcare workers (HCWs) play a decisive role during epidemics in transmitting accurate information to the public and motivating them to pursue protective behaviours, including immunisation. Methods: A cross-sectional survey-based study was conducted in the Czech Republic in September 2022 to evaluate HMPXV-related knowledge and vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 43 publications
4
54
3
Order By: Relevance
“…Moreover, the worrying state along with the increased awareness of mpox also reminds all community health professionals to focus on psychological issues related to health education. Previous study findings suggested that suboptimal level of mpox-related knowledge could be accompanied by a high proportion of vaccine hesitancy among healthcare workers ( 45 ). It's urgently needed to conduct further investigations on the impact of public awareness, knowledge, and worry on attitudes toward mpox vaccination based on the present study sample of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the worrying state along with the increased awareness of mpox also reminds all community health professionals to focus on psychological issues related to health education. Previous study findings suggested that suboptimal level of mpox-related knowledge could be accompanied by a high proportion of vaccine hesitancy among healthcare workers ( 45 ). It's urgently needed to conduct further investigations on the impact of public awareness, knowledge, and worry on attitudes toward mpox vaccination based on the present study sample of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the participants showed a low median knowledge score (4.0 out of 15.0, with around half of them knowing the mpox mode of transmission and its symptoms. The general population’s knowledge about mpox was assessed in various studies, including in the Kurdistan-region of Iraq, Lebanon, and Czech, where it was found that those studies participants had insufficient knowledge [ 21 , 23 , 24 ]. While in studies conducted in Saudi Arabia and Jordan, the participants had satisfactory knowledge [ 3 , 4 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with similar studies conducted in eight Middle Eastern countries [ 20 ], as well as in the Kurdistan region of Iraq [ 21 ], Lebanon [ 23 ] and Saudi Arabia [ 4 ]. Additionally, in Czeck, social media was the second-most utilized source of information about human mpox [ 24 ]. The increase in the reliance on social media platforms as a source of health-related information needs to be addressed by governments and healthcare providers because these platforms are not a reliable source of health information [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research instrument was adapted from previous studies [ 19 , 20 , 21 ]. The questionnaire was drafted in English and designed using Google Forms.…”
Section: Methodsmentioning
confidence: 99%